Chemistry : The molecular nature of matter and change - Silberberg, Martin S.; Duran, Randy; Gold, L. Peter; Haas, Charles G.; Loeschen, Robert L.; Norman, Arlan D. ([S.l.] : Mcgraw-Hill College, 2000)
This is a general chemistry text for the two-semester course. Silberberg offers a logical and unique approach to problem-solving, ground-breaking visualization of atomic/molecular interactions, and essential connections between chemical principles and real-world processes.
Keywords: chemistry,molecular,nature,matter